Aerobiological study of bacterial and fungal community composition in the atmosphere of Mexico City throughout an annual cycle - Del Carmen Calderon-Ezquerro, M.; Serrano-Silva, N.; Brunner-Mendoza, C.
The atmosphere as a temporary habitat for airborne microbial communities is a valuable topic to explore, and it is through aerobiological studies that the diversity of biological particles and their release, emission, transport, deposition, and impact are assessed. Specific microorganisms are involved in meteorological processes, and phytosanitary and public health concerns. Airborne microbial composition is related to factors such as geographic region and weather conditions. In this study a metagenomic approach was used to determine the composition of bacterial and fungal communities in the air of two different land-use areas (urban area and semi-rural area), during dry and rainy seasons in Mexico City. Air sampling was carried out with a Hirst-type spore trap, collecting the samples simultaneously in both study areas. Forty-two bioaerosol samples were collected, and the DNA obtained was sequenced using Next-Generation Sequencing. The results indicated that the bacterial communities were represented mainly by the phyla Actinobacteria, Proteobacteria, Firmicutes, Bacteroidetes, Cyanobacteria, and the fungal communities by the phyla Ascomycota followed by Basidiomycota. The evident changes in microbial composition were related more to seasonality than to locality, since both UA and SRA showed a high degree of urbanization, despite some differences in land use. Continuous monitoring of atmospheric bioaerosols is essential to determine the influence of meteorological factors on the composition of the aerial microbiota.
Keywords: BIOAEROSOLS; MICROBIAL COMMUNITIES; NEXT-GENERATION; SEQUENCING; SEASONAL VARIATION